An Adaptation of Pavlovian-to-Instrumental Transfer (PIT) Methodology to Examine the Energizing Effects of Reward-Predicting Cues on Behavior in Young Adults - da Costa, Raquel Quimas Molina; Furukawa, Emi; Hoefle, Sebastian; Moll, Jorge; Tripp, Gail; Mattos, Paulo (Frontiers in Psychology, 2020)
There is growing recognition that much of human behavior is governed by the presence of classically conditioned cues. The Pavlovian-to-Instrumental Transfer (PIT) paradigm offers a way to measure the effects of classically conditioned stimuli on behavior. In the current study, a novel behavioral task, an adaptation of the PIT framework, was developed for use in conjunction with an fMRI classical conditioning task. Twenty-four healthy young adults completed 1) instrumental training, 2) Pavlovian conditioning, and 3) a Transfer test. During instrumental training, participants learned to apply force to a handgrip to win money from slot machines pictured on a computer screen. During Pavlovian conditioning, slot machines appeared with one of two abstract symbols (cues), one symbol was predictive of monetary reward. During the Transfer test, participants again applied force to a handgrip to win money. This time, the slot machines were presented with the Pavlovian cues, but with the outcomes hidden. The results indicated an increased effort on the instrumental task, i.e., higher response frequency and greater force, in the presence of the reward-predicting cue. Our findings add to the growing number of studies demonstrating PIT effects in humans. This new paradigm is effective in measuring the effects of a conditioned stimulus on behavioral activation.